2020
DOI: 10.1186/s13287-020-02028-4
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine stimulation of perinatal lung functional and structural maturation by mesenchymal stem cells

Abstract: Background Mesenchymal stem cells (MSCs) were shown to harbor therapeutic potential in models of respiratory diseases, such as bronchopulmonary dysplasia (BPD), the most common sequel of preterm birth. In these studies, cells or animals were challenged with hyperoxia or other injury-inducing agents. However, little is known about the effect of MSCs on immature fetal lungs and whether MSCs are able to improve lung maturity, which may alleviate lung developmental arrest in BPD. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 76 publications
1
20
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) have demonstrated therapeutic potential in animal models of neonatal lung disease ( 21 23 ) and thus represent a promising future therapeutic approach to alleviate disease burden in preterm infants. In our previous study we determined the paracrine effect of MSCs on lung functional and structural development in FDLE cells and fetal lung explants ( 19 ). Herein we aimed at reproducing the reactivity of LOs in comparison to the prior study and to extend the knowledge about cellular effects of MSCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells (MSCs) have demonstrated therapeutic potential in animal models of neonatal lung disease ( 21 23 ) and thus represent a promising future therapeutic approach to alleviate disease burden in preterm infants. In our previous study we determined the paracrine effect of MSCs on lung functional and structural development in FDLE cells and fetal lung explants ( 19 ). Herein we aimed at reproducing the reactivity of LOs in comparison to the prior study and to extend the knowledge about cellular effects of MSCs.…”
Section: Resultsmentioning
confidence: 99%
“…The umbilical cord tissue was collected after delivery from human newborns whose mothers granted informed consent. MSC isolation and characterization are described elsewhere ( 19 ). MSC-CM was produced by incubating the culture medium with MSCs for 72 h, followed by sterile filtration.…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic activity in male and female FDLE cells stimulated with EGF was determined with 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays as described before 31 .…”
Section: Methodsmentioning
confidence: 99%
“…This explains the evident improvement of alveolarization, angiogenesis and pulmonary arterial remodeling by cell-free therapy with MSC-conditioned media in another meta-analysis of preclinical studies [ 237 ]. One very recent study reported on the effect of MSC-conditioned media on structural and functional lung maturation, therefore targeting the lung tissue immaturity itself [ 238 ]. The network-meta-analysis still found MSC therapy superior to MSC-conditioned media regarding all four analyzed clinically relevant outcomes (alveolarization, lung angiogenesis, pulmonary hypertension and lung inflammation) [ 235 ].…”
Section: What Is the Evidence For?mentioning
confidence: 99%